Microwaved-induced co-pyrolysis of used engine lubricant and palm empty fruit bunch for alternative fuel recovery - Nivasini Paramasivam; Rubia Idris; Chooi Wen Tan; William Woei Fong Chong; Guo Ren Mong; Jahimin A. Asik; Atikah Ali; Nur Wahida Fatini Aidy; Fadzlita Mohd Tamiri; Siti Rahayu Mohd Hashim; Cheng Tung Chong (Elsevier B.V., 2024)
Alternative fuel recovery from used engine lubricant (UEL) and empty fruit bunch (EFB) was achieved through microwave co-pyrolysis. Co-pyrolysis was chosen for its potential to improve the quality of pyrolytic oil by generating synergistic effects between two distinct feedstocks, reducing activation energy, and enhancing pyrolytic oil quality. The central composite design (CCD) of response surface methodology (RSM) was used to optimise the temperature and EFB ratio. Atomic absorption spectrometry (AAS) was employed to characterise the heavy metal concentration in the pyrolytic oil. The optimised pyrolytic oil (UE450) produced the highest oil yield (25.17 wt%) with the lowest metal concentration at 450 ◦C with a 50 % EFB ratio. The fuel’s characteristics were similar to those of conventional diesel, with a higher value of HHV (45.17 MJ/kg). However, the oil was slightly acidic, with a pH of 4.3. GC–MS analysis of UE450 revealed the presence of alkanes and monoaromatic-rich hydrocarbons. Additionally, the UE450 biochar was characterised using FTIR, FESEM, and XRF. FTIR analysis showed that the carbonyl group (C = O) peaks at 1730 and 1440 cm− 1 disappeared, indicating that heavy metals were bound to the biochar surface. Likewise, XRF analysis of UE450 biochar revealed that zinc (Zn) exhibited a high metal adsorption capacity, following the sequence Zn > Fe > Pb (1.96, 1.06, and 0.81 mmol/g). The XRF results also indicated a significant removal of SO3 at approximately 10.37 mmol/g.